Awareness and Use of Cloud Computing Services by Librarians in Selected Universities in Edo State - AIYEBELEHIN, AFEBUAMEH JAMES; MAKINDE, Bosede; Odiachi, Rosemary; MBAKWE, Chiamaka Cynthia (International Journal of Knowledge Content Development & Technology, 2020)
This study examined the awareness and use of cloud computing services by librarians in selected universities in Edo State. Descriptive survey research design was employed and the instrument used was questionnaire. The population of the study was 132 professional and Para-professional librarians. The total enumeration technique was used to select the entire population because the size was manageable. Simple percentage, frequency count and mean were used to analyze the data collected. From the analysis of data gathered, it was found that the librarians are aware of the use of OCLC, world cat and Google docs to a very high extent. It was found that the librarians used cloud computing services for collection development functions, and cataloging. Based on the findings it was recommended that management of the libraries should support librarians by providing constant internet connections, constant power supply, adequate funding of the library for effective and efficient service delivery. URL: http://ijkcdt.net/xml/24903/24903.pdf